Synthesis and Spectral Characteristics of 5-Amino-4-Cyanoimidazoles from Amidines - Yahyazadeh, Asieh; Eslamparast, Mehran (Asian Journal of Chemistry, 2016)
Imidazole derivatives have been synthesized in high yields by reaction between amidine and strong base depending on reaction conditions and mainly on the nature of the base used to induce cyclization.